2008
DOI: 10.1111/j.1750-3639.2008.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Layered Structure Shared Between Lewy Bodies and Lewy Neurites—Three‐Dimensional Reconstruction of Triple‐Labeled Sections

Abstract: Lewy bodies (LBs) and Lewy neurites (LNs) are the hallmarks of Parkinson's disease (PD). Although LBs and LNs, frequently coexistent, share some histological properties, their appearances are quite different under conventional two-dimensional observation. In order to clarify how these apparently different structures (LBs and LNs) are related during their formation, we performed three-dimensional observation on post-mortem brainstem tissues with PD. Sixty-microm thick floating sections were multi-immunofluorola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 44 publications
(70 reference statements)
6
50
0
1
Order By: Relevance
“…'Pale bodies', rounded areas of granular, pale-staining eosinophilic material displacing neuromelanin in brainstem neurons, are considered precursors of LBs [21]. LBs are associated with coarse, dystrophic ''Lewy neurites'' which may evolve into LBs [51]. All these Lewy structures share immunocytochemical and biochemical characteristics, the major components being aggregated aSyn, ubiquitin (Ub), phosphorylated neurofilaments, PARKIN, components of the ubiquitinproteasome system, molecular chaperons, and lipids (see [41,45,91]).…”
Section: Formation Of Lewy Bodiesmentioning
confidence: 99%
“…'Pale bodies', rounded areas of granular, pale-staining eosinophilic material displacing neuromelanin in brainstem neurons, are considered precursors of LBs [21]. LBs are associated with coarse, dystrophic ''Lewy neurites'' which may evolve into LBs [51]. All these Lewy structures share immunocytochemical and biochemical characteristics, the major components being aggregated aSyn, ubiquitin (Ub), phosphorylated neurofilaments, PARKIN, components of the ubiquitinproteasome system, molecular chaperons, and lipids (see [41,45,91]).…”
Section: Formation Of Lewy Bodiesmentioning
confidence: 99%
“…LBs are accompanied by dystrophic neurites, which according to recent 3-dimensional studies may evolve into LBs, with Ub at the core and neurofilaments at the outermost layer [655]. LB pathology [340,429,[663][664][665].…”
Section: Formation and Development Of As/lewy Pathologymentioning
confidence: 99%
“…However, these inclusions have distinctly different morphologies, with LBs being largely spherical whilst LNs have rod-or snake-like morphologies (Braak et al, 1999). Work by Kanazawa et al, using 3D reconstruction of confocal images revealed that both LB and LN share the same structural components of an inner filamentous α-syn and ubiquitin layer coated by neurofilament (Kanazawa et al, 2008), also finding LB/LN intermediary like structures sharing the same characteristics. This suggests LNs may be an earlier LB stage, thus explaining the abundance of these inclusions together in affected brain regions.…”
Section: Alpha-synuclein In Diseasementioning
confidence: 96%